Reliability and Validity Test of the Indonesian Version of the Hamilton Anxiety Rating Scale (HAM-A) to Measure Work-related Stress in Nursing - Iwan Muhamad Ramdan (Universitas Airlangga, 2019)
Introduction: Specific work characteristics have placed nurses as one of the professions with a high level of work-related stress. If not managed properly, work-related stress can cause adverse effects. Signs of stress can be seen in people's behavior, thinking or physical symptoms. One of a subjective measurement tool that is widely used to measure work-related stress is the Hamilton Anxiety Rating Scale (HAM-A), however, the literature that discusses the results of the HAM-A translation, validity and reliability test in the nurse profession is still limited. This study aims to translate HAM-A into the Indonesian version, then test its validity and reliability in nurses. Methods: A Cross-sectional study with stratified random sampling method was conducted on 98 nurses from July to August 2018. The English version of HAM-A consists of 14 items has been a translation into Indonesian version. Pearson Product Moment Correlation was used to evaluate the construct validity and Cronbach's alpha scores were used to assess the internal consistency reliability of the Indonesian version of HAM-A. Results: Item construct validity based on the Pearson correlation ranged from 0.529 to 0.727,  Cronbach's alpha reliability was obtained at 0.756. Conclusion:The Indonesian version of the HAM-A fulfills the criteria of a reliable (fair acceptable criteria) and valid (good criteria) assessment tool to assess the work-related stress in the nursing profession.